PECULIARITIES OF LEAD SULPHIDE AND NITRATE NANOPARTICLES INFLUENCE ON ORGANISMS OF EXPERIMENTAL ANIMALS IN DIFFERENT RESEARCH PERIODS AND METHODS OF ITS NEGATIVE IMPACT CORRECTION - Алексійчук, В.Д.; Сокуренко, Л.М.; Омельчук, С.Т. (World of Medicine and Biology, 2015)
The aim of our research was to study peculiarities of different size lead sulphide and nitrate nanoparticles influence on blood serum biochemical indices, morhpometric, densitometric indices of experimental animals’ hepatocytes nuclei and cytoplasm in different research periods and to elaborate guidelines of its alimentary correction. Studies were conducted in Wistar rats of 160-180 g body weight. Studied preparations were injected via intraperitoneal introduction daily 5 times per week (modeling of working week). Animals were distributed on 4 groups (60 animals each). First group of animals (PbSnano1) was treated with colloid solution of 10 nm lead sulphide nanoparticles at doses of 1.08 mg/kg body weight. Second group of animals (PbSnano2) was treated with colloid solution of 30 nm lead sulphide nanoparticles at doses of 1.08 mg/kg body weight. Third group of animals (Pb(NO3)2) was treated with solution of ionic lead nitrate at doses of 1.5 mg/kg body weight. Fourth (control) group of animals was treated with 1 ml of normal saline solution. Four series of experiments were carried out. Studied preparations were injected 30 times during 6 week period in the first set; studied preparations were injected 60 times during 12 week period in the second set; long-term effects after 6 weeks (post-exposition period) were studied in the third set; long-term effects after 6 weeks of simultaneous 60 injections of studied preparations and “Galychpharm” Thiocetam oral administration in fodder at doses of 250 mg/kg (30 times) were studied in the fourth set (18 week totally). 15 rats of each group were euthanized via decapitation in mild ether anesthesia after exposition period. Experimental animals’ blood serum and histological mounts of liver fixed preparations were test materials. Total protein, glucose, and total lipids blood serum levels were determined by Vitros-250 biochemical analyzer. Morphometric tests were conducted by image analyzer consisted of Olympus BX51 microscope equipped with C-4040zoom digital camera and personal computer. Statistical analysis of the measurement results was performed using Statistica 4.0 (Statistica Inc. USA), Biostat and MS Excell statistical software package. Compliance with the normal distribution characteristics was tested using Shapiro-Wilk test. Differences between the groups were established using parametric Student's t-test with normal distribution and non-parametric Mann-Whitney test, Wilcoxon and Kolmogorov-Smirnov in the absence of evidence of distribution normality.The effects of lead particles of 10 nm, 30 nm and 400 nm on biochemical indices of experimental animals’ blood serum were studied in animal experiments. It was found that a protein, lipid and carbohydrate metabolism disorders were developing in rats injected with a solution of PbS nanoparticles of 10, 30 nm and a solution of Pb (NO3)2 with a particle size of 400 nm for 6 and 12 weeks. Ebbing of these substances influence and Thiocetam positive effects on protein, lipid and carbohydrate metabolism, and densitometric and morphometric indices of hepatocytes nuclei and cytoplasm were noticed at post-exposition period. Recommendations for nutritional correction of lead nanoparticles possible adverse effects on workers’ health were elaborated.
Keywords: lead sulphide nanoparticles; Thiocetam; rats; protein; lipid and carbohydrate metabolism